Psychological stress enhances tumor growth and diminishes radiation response in preclinical model of lung cancer. (May 2020) - Zhang, Yi; Zanos, Panos; Jackson, Isabel L.; Zhang, Xiuwu; Zhu, Xiongzhao; Gould, Todd; Vujaskovic, Zeljko
Highlights: Psychological stress-induced depression increased tumor growth and radioresistance. Psychological stress activates epithelial-mesenchymal transition associated with resistance. Psychological stress increased tumor growth and radioresistance via adrenergic receptors. Abstract: Background and purpose: Patients with life-threatening illnesses, such as cancer, experience emotional distress. This study was to investigate the molecular and cellular mechanisms of relevant psychological stressor on tumor growth and therapeutic resistance. Materials and Methods: Stress was induced in C57BL/6J mice bearing LLC lung tumors by exposure to a conspecific mice receiving inescapable foot shocks. Mice were irradiated at 7 Gy for 3 consecutive days. Behaviors were monitored by open field test (OFT), elevated plus maze (EPM), sucrose preference test (SPT), and learned helplessness (LH) test. Protein expression in tissues and cultured cells were measured by Western blot. Results: This study in animals showed that observing a conspecific mouse receiving foot shocks induced depression like behaviors with increased plasma corticosterone and adrenaline levels which increased tumor growth and radioresistance. Stress increased Wnt1, Drosha, and vimentin expression and decreased E-cadherin expression in tumor tissues. The combination of stress and irradiation enhanced radioresistance along with the increase in vimentin expression. The in vitro study showed that a β2 -adrenergic receptor (β2-AR) agonist blocked irradiation-induced cell apoptosis and decreased cell viability, while silencing β2-AR expression reduced the protective effects of β2-AR agonist. β2-AR agonist obviously increased Wnt1 and Drosha expression in LLC-1 cells. Conclusion: Psychological stress increased tumor growth and enhanced radioresistance associated with the activation of epithelial-mesenchymal transition by stress hormone-stimulated adrenergic receptors.